(untitled) (PERcursos Linguísticos, 2024)
ABSTRACT: Like a significant part of the population, teachers also see people with disabilities (PWDs) as unfamiliar or different. This behavior is shaped by a colonizing, planning, dualistic, and abysmal logic (Santos, 2010) that seeks to make their differences, bodies, histories, knowledge, and experiences invisible. Teachers play a fundamental role in implementing inclusion policies; therefore, it is necessary to problematize this resistance that prevents teachers from fulfilling their role as professionals and citizens. The aim of this work is, using experiential accounts, to share experiences in inclusive education that reveal prejudice and tensions, but also the taking of ethical responsibility for the other. We rely on decolonial theory, Levinas’ philosophy, and Freire (2022 [1996]) who invites us to think correctly. The reflections made in this study point to the recognition of subjects as well as their otherness and the (pre)valence of ethics, as advocated by Levinas (1998). We hope that this work will promote critical approaches and desirable bridges between the various subjects and our pedagogical practice. KEYWORDS: Inclusive education. People with disabilities (PWD). Ethics. Decoloniality. Narratives.